Climate Policy Commitment at the Municipal Level in Germany – Development of an Index on Awareness, Conception and Implementation of Climate Mitigation and Climate Adaptation - Zorn, Anika; Tafel, Julian; Schäfer, Susann (Raumforschung und Raumordnung | Spatial Research and Planning, 2024)
This paper presents an additive index on climate policy engagement at the municipal level, based on the three dimensions awareness, conception and implementation of climate change mitigation and adaptation. The distortion of the index is based on the self-perception and personal assessment of municipal decision-makers, which were collected and evaluated as part of a primary survey (postal survey). The index shows how strongly a municipality is committed to climate policy. Thus, it represents an extension of previous indices that either only consider climate mitigation or adaptation or are only based exclusively on secondary statistics. The second part of the paper describes the application of the index in three counties or 51 municipalities in Saxony, Saxony-Anhalt and Thuringia. The interpretation takes place in the context of structural characteristics of the municipalities concerned (number of inhabitants, share of votes of different parties, geographical location). The distribution of the index values shows a similar awareness in climate protection and climate change adaptation, but an increasing discrepancy in the implementation of adaptation-specific measures.